Manifest Trauma and Remembering Sorrowful Terroristic Life in Dikpal’s “Liwang 2006” - Badri Prasad Pokharel (Interdisciplinary Journal of Management and Social Sciences, 2022)
This article is an attempt to study different aspects of trauma in Rajkumar Dikpal’s story “Liwang 2006” with the help of psychological trauma and its major assets. The story is written on the background of ten years long civil war which caused the death of more than fifteen thousand people and millions of others remained homeless for a long time. Among many wars affected people, Purnaman, Dilsara Ghartimagar, Bainsamali, the main characters in the story, are the people who become victims of the insurgency and have to go through painful traumatic situation. This paper tries to show how they become traumatized and how severely they go through this situation. For this, the major assets of Caruth and other trauma theorists as theoretical tool have been applied to analyze the trauma and its post-traumatic stress disorder found in the primary text, “Liwang 2006”. Here, the story has been analyzed keeping traumatic aspects, which would, subsequently, help one understand personal trauma and its aftermath as well the conflict which badly affect the lives of people living in the hinterland of the nation. By bringing out the outcomes of the conflict and its bad results, this article centers on the common people’s painful traumatic condition due the civil war and how those who remain alive are seen remembering those sorrowful terroristic life in past.